2010
DOI: 10.1007/s00339-010-5822-x
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring of thin films by ns pulsed laser interference

Abstract: We show that nanosecond pulsed laser interference can be used to structure surfaces on a nanoscale. With this method, we are able to create hollow structures on various thin films like Ta, Ni, Au, Cu, Co, and NiTi. We find that the structuring mechanism is related to the mechanical effect of thermal expansion upon melting. To corroborate this model, we study materials with an abnormal behavior at the melting point like Si, Ge, or Bi, as they contract upon melting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…First we show the results of the group of materials that behave similar to former results by other groups [6,8]. For these materials (Si, Bi, Ge) we found that the dewetting leads to areas which are free of metal ( Fig.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…First we show the results of the group of materials that behave similar to former results by other groups [6,8]. For these materials (Si, Bi, Ge) we found that the dewetting leads to areas which are free of metal ( Fig.…”
Section: Resultssupporting
confidence: 77%
“…As we pointed out earlier [8] the formation of the membrane is connected to the expansion of the liquid upon melting. If the expansion upon melting cannot be neglected the metal gains vertical interia upon melting which might lead to detachment from the surface in the case of low adhesion.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…In comparison to these methods laser interference lithography offers the opportunity for fast and flexible realization of periodic structures over macroscopic area in a single processing step [4][5][6][7][8]. In laser interference lithography periodic structures are created either in a photoresist layer covering the material surface [8] or, when high energy lasers are used, directly in the material of interest [4][5][6][7]. In the latter technique, called direct laser interference lithography (DLIL), the superposition of coherent laser beams, originating from the same source, locally modifies the properties of irradiated materials.…”
Section: Introductionmentioning
confidence: 99%
“…12 It has been clarified that a flow of Si melt (capillary wave) is responsible for formation of columns or cones and that their growth is promoted by reactive gases. [13][14][15][16] A regular arrangement of these columns and cones has also been studied extensively; e.g., installation of a photomask [17][18][19] or a microlens array (glass spheres) 20,21 on a Si plate, spatial modulation of a laser beam by use of a liquid-crystal cell, 5 interference-fringe formation by multi-beam irradiation, 22 and successive irradiation of two beams with orthogonal polarization directions. 23,24 Whereas laser irradiation is usually achieved in vacuum or a gas phase (air, inert or reactive gas), a liquid-phase processing is currently attracting interests for constructing more refined textures.…”
Section: Introductionmentioning
confidence: 99%